Clinical Versus Research Sequencing - Shevchenko, Yuriy (Cold Spring Harb Perspect Med, 2016)
Historically, sequencing has been the key technology to assess variation in the genetic code, and has been widely accepted in clinical diagnostics of genetic disease. The advent of next-generation sequencing (NGS) methods increased the size of the analyzed target by several orders of magnitude, while at the same time drastically reducing the cost of sequencing. Current research allows sequencing of germline and tumor whole genomes. However, with the arrival of cutting-edge technology to the clinical diagnostic field, strict regulatory oversight is required to use the advances of the latest research when applied to routine clinical practice. We discuss the differences between sequencing in a research setting and sequencing in a clinical diagnostics setting, as applied to next-generation technology.